The Relationship between Sexual Self-Efficacy and Sexual Function in Married Women - Mahboubeh Kafaei Atrian; Zahra Mohebbi Dehnavi; Zahra Kamali (Mashhad University of Medical Sciences, 2019)
Background & aim: Sexual self-efficacy refers to the belief of each individual about his/her ability to be sexually active, his/her desirability for sexual partner, and assessment of the ability and self-efficacy in sexual behavior. Sexual relationship is one of the key pillars of a successful family; accordingly, functionality in this domain largely affects marital satisfaction. The aim of this study was to determine the relationship between sexual self-efficacy and sexual function among married women. Methods: This descriptive-correlational study was conducted on 201 married women referring to the clinic of Lenjan Hospital, Isfahan in 2017. The study population was selected through convenience sampling. The women scoring below 40 in the Beck Depression Inventory were entered into the study and filled out the questionnaires of sexual self-efficacy and sexual function. The data were analyzed in SPSS software (version 22) using descriptive statistics and Spearman's rank correlation coefficient. Results: The mean age of participants was 32±6.70 years, and their mean menarche age was 12±36.1 years. The mean scores of sexual function and sexual self-efficacy were obtained as 26.17±1.44, 21.54±2.70, respectively. The results revealed a positive correlation between sexual self-efficacy and sexual function (r=0.205, P=0.001). Also, sexual self-efficacy showed a significant relationship with some subscales of sexual function, including libido, orgasm, lubrication, and sexual arousal (P≤0.05). Conclusion: Sexual self-efficacy had a positive relationship with some of the subscales of sexual function. Therefore, sexual function in women can be strengthened by the enhancement of their sexual self-efficacy.